Formalizing argument-based agent interaction in electronic institutions - Chesñevar, Carlos Iván (2001)
During the last decade the notion of agent has gained acceptance within the AI community, mainly due to its adequacy to formalize complex environments. Agents can be thought as active software objects, which may be autonomous and able to perceive, reason, act, and interact with other agents. When agents interact with each other, a multi-agent system (MAS) arises.